Hubungan self control dengan perilaku konsumtif belanja online pada mahasiswa rantau - Laura Putri Anggraini; Hudaniah, Hudaniah (Cognicia, 2023)
Abstract. Technological advances have brought changes in various aspects of life, including shopping. Various online shopping sites appear and make it easier for someone to make a purchase If migrate students do online shopping, if it is not accompanied by good self-control, it can give rise to consumerist behavior. If online shopping activities carried out by overseas students are not balanced with good self-control, it will lead to consumptive behavior. The purpose of this study was to find out whether there is a correlation between self-control and consumptive behavior in online shopping among overseas students. This study used a correlational quantitative approach with 358 respondents as subjects. Sampling was carried out using a purposive sampling technique with the criteria are overseas students who are studying outside the city, aged 18-24 years, and routinely shop online at least once a month. The instruments used in this research are the self-control scale and the consumptive behavior scale. Data analysis in this study used Spearman’s rank correlation. The results showed that there was a negative relationship between self-control and online shopping consumptive behavior among overseas students because p=-0,521 and p=0,000 < 0,05 was obtained. This shows that the higher the self-control of overseas students, the lower the consumptive behavior and otherwise. Keyword: Consumptive behavior, overseas student, self control